Information and communications technology in primary school education - Sarkar, Subrata; Mohapatra, Sanjay; Sundarakrishnan, J. (Springer, 2017)
This book illustrates approaches for implementing ICT in primary education. Through different initiatives and case studies, the book shows different approaches for successful implementation of ICT. While it gives details of theoretical concepts related to ICT, it also provides live examples from different initiatives as to how literacy can be achieved through customized implementation strategy. The book illustrates different ICT policies that have been implemented with varying degree of success. It also demonstrates different approaches that would be of interest to practitioners. About the Authors Subrata Sarkar has a Masters in Political Science with a specialization in Political Sociology and an additional specialization in International Relations including Defense and Strategic Studies. He also has a Bachelors in Law. His research interests are in the field of application of technology in education. He has more than 21 years of experience in education, action research and development field. He is currently heading the Digital Equalizer Program in Odisha as Operations Director with American India Foundation. Dr. Sanjay Mohapatra has done B.E. from NIT Rourkela, M. Tech from IIT Madras, PGDBM XIMB, India and has finished his Ph. D. from Utkal University, India under Management Department. At present, he is an Associate Professor in Information Systems in XIMB, India. Professor Mohapatra has more than 21 years of industry experience. He has worked in various capacities in organizations like Hindustan Aeronautics Limited, Larsen & Toubro, PricewaterHouse, Infosys, Polaris & J & B Software. His teaching interests are in IT Strategy and Management Information Systems and research interests are in the area of IT enabled processes. He has authored/co-authored nine books and more than twenty papers in peer reviewed international journals. J Sundarakrishnan has an MSc in Electronics, University of Delhi and also holds a Masters in Business Administration from the Faculty of Management Studies, Delhi. He has worked extensively in the development field. His work is aligned with Millennium Development Goals in increasing literacy rate in India. He is currently working in the capacity of Country Director, Digital Equalizer (DE), American India Foundation.
Keywords: Educational technology.; Education, Elementary -- Computer-assisted instruction.; elektronické knihy; electronic books